The Analysis Of Implementation Of The Independent Curriculum In Elementary Schools - Wahyu Pertiwi, Monica; Tadzkiroh, Ummi; Sumardjoko, Bambang; Ghufton, Anik (Perspektif Ilmu Pendidikan, 2023)
This research is to find out and examine the "Analysis of the Implementation of Independent Curriculum in Mobilizing Schools SDN Kartasura 02 This research was conducted using a phenomenological approach. This type of research is qualitative research that looks at and hears closer and detailed explanations and individual understanding of their experiences. The phenomenological approach is based on the researcher's interest in studying more deeply the phenomena experienced by key informants. The research was conducted at SDN Kartasura 02.. Informants in this study were teachers, principals, supervisors. Collection The data was collected using several techniques, namely; (a) observation, (b) interviews, and (c) documentation study. To ensure the validity of the data, several efforts were made as follows: (a) extending the data collection period, (b) conducting direct observation constantly and seriously, (c) triangulating, and (d) involving colleagues to discuss. From the results of the study in this study, it was found that there was an independent curriculum which was used as a reference in driving schools, which produced students who had noble character, were independent, reasoned critically, were creative, gotong royong, and had a sense of diversity. The driving school principal encourages a variety of participatory, unique, and many innovative programs. Fostering cooperation with teachers who support their leaders to participate in realizing driving schools.